The golden honeymoon - Wright, Teresa; Whitmore, James, 1921-2009; Elliott, Stephen; Black, Noel; Lardner, Ring, 1885-1933 (American short story collection., 1986)
The story of an elderly couple who takes a winter vacation in St. Petersburg, Florida in the 1920's, and discovers that 50 years of marriage have not prevented the arousal of old jealousies nor diminished the chances of an even deeper love.